Forward acceleration of the centre of mass during ski skating calculated from force and motion capture data - Göpfert, C.; Pohjola, M. V.; Linnamo, V.; Ohtonen, O.; Rapp, W.; Lindinger, S. J. (Sports Engineering, 2017)
The purpose of this paper was to present and evaluate a methodology to determine the contribution of bilateral leg and pole thrusts to forward acceleration of the centre of mass (COM) of cross-country skiers from multi-dimensional ground reaction forces and motion capture data. Nine highly skilled cross-country (XC) skiers performed leg skating and V2-alternate skating (V2A) under constant environmental conditions on snow, while ground reaction forces measured from ski bindings and poles and 3D motion with high-speed cameras were captured. COM acceleration determined from 3D motion analyses served as a reference and was compared to the results of the proposed methodology. The obtained values did not differ during the leg skating push-off, and force-time curves showed high similarity, with similarity coefficients (SC) >0.90 in the push-off and gliding phases. In V2A, leg and pole thrusts were shown to contribute 35.1 and 65.9% to the acceleration of the body, respectively. COM acceleration derived from ground reaction forces alone without considering the COM position overestimated the acceleration compared to data from motion analyses, with a mean difference of 17% (P < 0.05) during leg push-off, although the shapes of force-time curves were similar (SC = 0.93). The proposed methodology was shown to be appropriate for determining the acceleration of XC skiers during leg skating push-off from multi-dimensional ground reaction forces and the COM position. It was demonstrated that both the COM position and ground reaction forces are needed to find the source of acceleration.